Phosphorylation of receptor-like cytoplasmic kinases by bacterial Flagellin - Lu, Dongping (Landes Bioscience, 2010)
Molecular mechanisms that distinguish self and non-self are fundamental in innate immunity to prevent infections in plants and animals. Recognition of the conserved microbial components triggers immune responses against a broad spectrum of potential pathogens. In Arabidopsis, bacterial flagellin was perceived by a leucine-rich repeat-receptor-like kinase (LRR-RLK) FLS2. Upon flagellin perception, FLS2 forms a complex with another LRR-RLK BAK1. The intracellular signaling events downstream of FLS2/BAK1 receptor complex are still poorly understood. We recently identified a receptor-like cytoplasmic kinase (RLCK) BIK1 that associates with flagellin receptor complex to initiate plant innate immunity. BIK1 is rapidly phosphorylated upon flagellin perception in an FLS2- and BAK1-dependent manner. BAK1 directly phosphorylates BIK1 with an in vitro kinase assay. Plants have evolved a large number of RLCK genes involved in a wide range of biological processes. We provided evidence here that additional RLCKs could also be phosphorylated by flagellin and may play redundant role with BIK1 in plant innate immunity.